Occupational safety and health for technologists, engineers, and managers - Goetsch, David L.
Known for its comprehensive coverage, this text covers all aspects of occupational safety and health in today's global workplace. Appropriate for safety management, engineering and technology programs, the book follows a logical sequence that provides a historical perspective and overview, covers the laws and regulations, discusses the human element, examines hazard assessment, prevention, and control, and covers management of safety and health. This edition features updated OSHA standards and contemporary topics such as safety culture, safety's role in global competitiveness, workplace violence, natural disasters and terrorism.